Determination of badminton players' displacement by video analysis: Reliability results of manual measurements - Sarro, K. J.; Chiminazzo, J. G. C.; Cabello-Manrique, D.; Misuta, M. S. (6th World Congress of Racket Sport Science, Bangkok, 25.-26.05.2018, 2018)
Video analysis provides an unobtrusive way of collecting information about physical, technical and tactical demands during official competitions. This work presents the reliability results of the displacement of badminton players determined by manual measurement of video images.